The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
All Days 2006
DOI: 10.2118/101247-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for the Nonequilibrium Initialisation of Reservoir Models With Lateral and Vertical Variations in the Initial Fluid Composition

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractNew methods have been developed to initialise a compositional model for a giant Middle East reservoir where the initial H 2 S mol% varies laterally from close to 0 to around 20 and vertically from close to 0 to around 20, being highest at the lower parts of the reservoir.Conventional initialisation methods assume equilibrium, assigning the same composition to any grid block at a given depth. Two different new method, triangulation and surface-fit, are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The results of mole fractions further indicate that the light species flow to the top parts the domain while the dense components sediment to the bottom of the domain due to the effect of gravity. Figures 8,11,14,17,20,and 23 show the convergence process of total energy with time for the six groups of different orders. We still compute the total energy in species-wise at each time step in blue while the total energy in each full time step is shown in red.…”
Section: Figure 2 Mole Fractions At Different Timementioning
confidence: 99%
“…The results of mole fractions further indicate that the light species flow to the top parts the domain while the dense components sediment to the bottom of the domain due to the effect of gravity. Figures 8,11,14,17,20,and 23 show the convergence process of total energy with time for the six groups of different orders. We still compute the total energy in species-wise at each time step in blue while the total energy in each full time step is shown in red.…”
Section: Figure 2 Mole Fractions At Different Timementioning
confidence: 99%
“…Incomplete hydrocarbon migration can cause dynamic changes in the reservoir fluid composition with time and location in deposits. It has been observed that inflows of secondary fluid streams to the corners of a reservoir can cause changes in the fluid composition throughout the reservoir body.…”
Section: Introductionmentioning
confidence: 99%
“…Quando a densidade inicial do óleo varia horizontalmente, existe um pequeno desequilíbrio entre colunas adjacentes. Admite-se que as propriedades do óleo foram alteradas por alguma razão após a sua migração, não estando na realidade em perfeito equilíbrio no reservatório (Gibson, 2006; Dindoruk e Al Kindi, 2007). Pode-se, porém, observar por simulações, que o tempo necessário para que esse equilíbrio ocorra é infinitamente superior aos períodos de produção de um campo de petróleo.…”
Section: Inicializaçãounclassified